Signing with the Face: Emotional Expression in Narrative Production in Deaf Children with Autism Spectrum Disorder. - Denmark, Tanya; Atkinson, Joanna; Campbell, Ruth; Swettenham, John (Journal of Autism & Developmental Disorders, 2019)
This study examined facial expressions produced during a British Sign Language (BSL) narrative task (Herman et al., International Journal of Language and Communication Disorders 49(3):343-353, 2014) by typically developing deaf children and deaf children with autism spectrum disorder. The children produced BSL versions of a video story in which two children are seen to enact a language-free scenario where one tricks the other. This task encourages elicitation of facial acts signalling intention and emotion, since the protagonists showed a range of such expressions during the events portrayed. Results showed that typically developing deaf children produced facial expressions which closely aligned with native adult signers' BSL narrative versions of the task. Children with ASD produced fewer targeted expressions and showed qualitative differences in the facial actions that they produced.